(untitled) (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
‘Decolonising multilingualism in Africa: recentering silenced voices from the global South’ published by Multilingual Matters offers fresh accounts of key concepts in the field of multilingualism from an African perspective. The authors, Finex Ndhlovu and Leketi Makalela, draw together the sociolinguistic mainstay ‘multilingualism’ and theories of decoloniality. This provokes a stimulating conversation in which ‘the multilingual and decolonial turns rub upagainst each other’ (xi). The book locates the conversation of how to decolonise multilingualism within an African setting, unapologetically offering the African linguistic context as a center from which to explore these concerns. The title of the book refers to this as a ‘recentring’ but in fact what this publication means is that the authors have placed Africa in the center of this corner of the academy for the first time.